New Polymeric Disulfonimide for Heterogeneous Silicon Lewis Acid Catalysis - Giorgianni, Giuliana; Casacchia, Maria Edith; Ricci, Pier Carlo; Di Muzio, Simone; Lazzarini, Andrea; Carlone, Armando; Pesciaioli, Fabio (Synlett, 2024)
A new heterogeneous polymeric disulfonimide was very easily synthesized from simple commercially available reagents. The new cost-effective catalytic material exhibited a tremendously enhanced reactivity in a benchmark Mukaiyama aldol reaction via silicon Lewis acid activation when compared with common acidic resins. Moreover, the reported polymeric disulfonimide exhibits outstanding robustness, as confirmed by its good thermal stability and excellent recyclability.
Keywords: heterogeneous catalysis; disulfonimides; organocatalysis; silicon Lewis acid catalysis; ionomers